2022
DOI: 10.1371/journal.pone.0267024
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficacy of the magnetic resonance T1w/T2w ratio for the middle cerebellar peduncle in multiple system atrophy and spinocerebellar ataxia: A preliminary study

Abstract: Background The standardized T1-weighted/T2-weighted (sT1w/T2w) ratio for the middle cerebellar peduncle (MCP) has been reported to be sensitive for detecting degenerative changes in the cerebellar subtype of multiple system atrophy (MSA-C), even in the early stages. We aimed to investigate the diagnostic value of the MCP sT1w/T2w ratio for differentiating between MSA-C and spinocerebellar ataxia (SCA). Methods We included 32 MSA-C, 8 SCA type 3 (SCA3), 16 SCA type 6 (SCA6) patients, and 17 controls, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Consistent with the current study results, our previous studies revealed that the MCP sT1w/T2w ratio can differentiate patients with early MSA-C from those with hereditary spinocerebellar ataxia [26,27]. Pathologically, reactive gliosis and the loss of axons and myelin are the MSA-related degenerative changes in the MCP [37], presumably reflected in the decreased MSA sT1w/T2w ratio [27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the current study results, our previous studies revealed that the MCP sT1w/T2w ratio can differentiate patients with early MSA-C from those with hereditary spinocerebellar ataxia [26,27]. Pathologically, reactive gliosis and the loss of axons and myelin are the MSA-related degenerative changes in the MCP [37], presumably reflected in the decreased MSA sT1w/T2w ratio [27].…”
Section: Discussionsupporting
confidence: 92%
“…Standardization of the T1w/T2w ratio (sT1w/T2w ratio) has been proposed, allowing for a meaningful comparison between subjects and scanners by creating scaled intensity while correcting for inhomogeneities in receiver coil sensitivity [25]. We previously reported that using the sT1w/T2w ratio for evaluating MCP can help detect early MSA-C-related degenerative changes (e.g., myelin loss), considering that it shows high diagnostic accuracy in differentiating patients with MSA-C from healthy individuals and those with spinocerebellar ataxia [26,27]. However, the usefulness of MCP sT1w/T2w ratio in differentiating between MSA-P and PD remains unreported.…”
Section: Introductionmentioning
confidence: 99%